Talk, Prevent, and Protect About Breast Cancer and Cervical Cancer - Rukmaini; Monalisa; Dufi Roma Dini; Nina Rahmawati; Aditya Suhartika; Euis Badriah; Sally Pratama; Nabila Husna; Anita Helena; Nuriani (Rajaki of Tulip Medika Publisher, 2026)
Breast cancer and cervical cancer remain major causes of morbidity and mortality among women globally, including Indonesian women living abroad. Limited health literacy, restricted access to screening services, and cultural as well as language barriers contribute to delayed detection, particularly among Indonesian migrant women in South Korea. This community service program aimed to improve knowledge, awareness, and preventive behavior related to breast and cervical cancer among members of the Indonesian Muslim women community (Rumaisa) in Seoul. The activity employed a participatory educational approach, including health education sessions, audiovisual presentations, group discussions, and practical early detection through routine screening and healthy lifestyle practices. Participants also demonstrated increased confidence in performing BSE and expressed willingness to disseminate the information to other community members. In conclusion, structured and community-based educational interventions are effective in enhancing health literacy and promoting preventive behaviors related to breast and cervical cancer. Continuous and sustainable health education programs are recommended to strengthen cancer prevention demonstrations of breast self-examination (BSE). Evaluation was conducted using pre-test and post-test questionnaires to assess changes in participants’ knowledge. The results showed a significant improvement in participants’ understanding of risk factors, early signs, prevention strategies, and the importance of efforts and reduce the burden of breast and cervical cancer among Indonesian migrant women.